Bone metastasis and skeletal-related events in patients with solid cancer: A Korean nationwide health insurance database study - Hong, Soojung (PLoS One, 2020)
Bone is one of the most common sites of metastasis from advanced solid tumors. Bone metastasis is a leading cause of pain and increases the risk of skeletal-related events (SREs) in cancer patients. In addition to affecting the quality of life, it also increases the medical costs and mortality risk. We aimed to examine the occurrence of bone metastasis and SREs in Korean cancer patients using a nationwide health database. Using claims data from the National Health Insurance Service-National Sample Cohort (2002–2013), we extracted the data of bone metastasis patients diagnosed with any of the seven major cancers in Korea from January 2002 to December 2010. Selected SREs included pathologic fracture, spinal cord compression, radiation therapy, and palliative bone surgery. We used time-to-event analysis to estimate patient survival after bone metastasis. A total of 21,562 newly diagnosed cancer patients were identified; bone metastases developed in 1,849 patients (breast cancer, 18.8%; prostate cancer, 17.5%; lung cancer, 13.7%). The median time from primary cancer diagnosis to bone metastasis was 18.9 months. The cumulative incidence of SREs was 45.1% in all bone metastasis patients. The most common cancer type was lung cancer (53.4%), followed by liver (50.9%), prostate (45.9%), breast (43.6%), and colorectal (40.2%) cancers. Almost all SREs developed 1 month after bone metastasis, except in patients with breast and prostate cancers (median: 5.9 months in breast cancer and 4.7 months in prostate cancer). Survival duration after the development of bone metastasis was < 6 months in stomach, liver, colorectal, and lung cancer patients. Breast and prostate cancer patients survived for > 1 year after the occurrence of SREs. This study reveals the epidemiology of bone metastasis and SREs in Korean cancer patients, and the findings can be used to assess the actual bone health status of cancer patients.